Determination of the Factors Preventing Students of the Faculty of Sports Sciences from Participating in Recreational Activities: Ondokuz Mayis University Sample - CEBG, Mehmet; CAVUgOGLU, Gul; UNVER, gaban; GSLAMOGLU, Gzzet; ACAR, KurGat (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The purpose of this study is to examine the factors which prevent the students of Faculty of Sport Sciences fromparticipating in recreational activities in terms of some variables.A total of 275 (183 men, 92 women) randomly chosen students studying at Ya?ar Do?u Faculty of Sport Sciences participated in the study voluntarily. “Leisure Constraints Questionnaire” developed by Alexandris and Carroll (1997)adapted to Turkish by Karaküçük and Gürbüz (2007) was used as the data collection tool. The data obtained wereanalyzed with SPSS 21 package program. Kolmogrov test was used to find out whether the data were normally distributed and the data were found to be normally distributed. The data were analyzed with frequency analysis, t test and Anova test in independent samples and the Bonferroni test was used to analyze the difference between groups.The factors which prevented students from participating in recreational activities showed significant differences in“individual psychological” subscale and total scores in terms of the variable of age and in “facilities/services andaccessibility” subscale in terms of gender (p<0,05). In terms of the difference in the age variable, participation in recreational activities increased as age increased. In terms of gender, women were seen to participate less in recreationalactivities when compared with men.The results of the study showed that the students of the Faculty of Sport Sciences did not have difficulties in participating in recreational activities; however, women were found to participate less than men. In order to increase women’sparticipation, informative activities, activities for women and interesting activities for women should be made moreattractive.